Energy Efficiency and Energy Saving in Public Schools: Federal Policy and Regional Perspectives from Russia - Neustroev, Sergey S.; Arinushkina, Anna A. (International Journal of Energy Economics and Policy, 2019)
In general, the paper addresses the challenge of high energy intensity of the public organization in Russia. In particular, the study aims to investigate the key aspects of energy efficiency and energy saving policies in public schools, which have been adopted at the federal level and implemented in the regions of Russia. The paper provides a legal review of these policies in order to analyze the existing mechanisms of increasing energy efficiency in public schools. The monitoring mechanisms of public schools' energy efficiency and saving policies is also critically reviewed. In order to comprehensively analyze certain challenges of increasing energy efficiency in public schools, the paper includes results of in-depth interviews with school principals of both urban and rural educational organizations from the Siberian Federal District. Relying on the best world experiences and advanced scholarship, the authors provide a number of recommendations that could help to increase and sustain energy efficiency in the Russian public schools. Keywords: Public School, Energy Efficiency, Energy Saving, Policy, Region, Russia. JEL Classifications: A29, I21, I25, Q38, Q48 DOI: https://doi.org/10.32479/ijeep.8582